Valorization of Dairy By-Products, Sweet Whey, and Acid Whey, in the Production of Fermented Black Carrot Juice: A Comparative Study of the Phytochemical, Physicochemical, Microbiological, and Sensorial Aspects - Hacer Çoklar; Mehmet Akbulut; Ali Aygun; Muhammed Talha Akbulut (Foods)
The aims of this study were to improve the functional and nutritional properties of fermented black carrot juice by using sweet and acid whey in the production of fermented black carrot juice, to transform whey into a value-added product and to determine the effect of whey addition on the fermentation process. Whey was utilized as a water substitute in the formulation of the beverage prior to fermentation, and five distinct formulations were developed based on the type and proportion of whey (0% whey (control sample), 25% acid whey, 100% acid whey, 25% sweet whey, 100% sweet whey). Microbiological, sensorial, phytochemical, and physicochemical analyses were performed on samples taken during fermentation and on samples fermented and then resting. The addition of whey into the formulation resulted in an increase in acidity and turbidity of the beverage, with lower anthocyanin content observed in samples containing whey compared to the control throughout the fermentation process. The samples containing 100% whey exhibited lower a*, b*, h, and C* values and lower amounts of individual anthocyanins. The microbial load in these samples was high in the early stages of fermentation and reached a minimum towards the end of fermentation. The incorporation of whey led to an acceleration in the fermentation process, an enhancement in the microbiological characteristics of the beverage, and a substantial variation in phenolic compounds through the formation of a reversible protein complex. The resting process provided significant increases in color, anthocyanins, and gentisic and chlorogenic acids of whey-containing samples. The results showed that it is possible to produce whey-based functional fermented black carrot juice that is close to the control sample in terms of sensory and phytochemical properties and better than the control sample in terms of lactic acid bacteria count. It is recommended that both sweet and acid whey be utilized at a ratio of 25% in the production of fermented black carrot juice and to rest at 4 °C before consumption.